Exporting under financing constraints: Firm-level evidence from EU countries - Gavin Murphya; Iulia Siedschlagb (The Economic and Social Research Institute (ESRI), 2016)
Financing constraints have been identified as an additional source of firm heterogeneity that affects export participation and export performance. This paper examines whether and to what extent financing constraints affect firms' exporting across different types of firms and industries. It uses comparable micro data from France, Germany, Italy and Spain and estimates the sensitivity of firms' extensive and intensive margins of exporting to financing constraints. The empirical results indicate that firms which were less constrained financially were more likely to export, while financing constraints did not affect the export intensity of existing exporters. It appears that financing constraints affect export participation via firms' productivity. The sensitivity of exporting to access to external financing appears to be most important for young, domestic-owned and firms in traditional industries. The sensitivity of the export propensity to financing constraints decreased with firm size.
Keywords: F14; F23; F65; G32; 330; Exporting; Financing Constraints; Firm Heterogeneity